Bank Efficiency, Ownership, And Market Structure : Why Are Interest Spreads So High In Uganda ? - Beck, Thorsten, 1967- 1967- (The World Bank, 2006)
Using a unique bank-level data set on the Ugandan banking system during 1999-2005, the authors explore the factors behind consistently high interest rate spreads and margins. While foreign banks charge lower interest rate spreads, they do not find a robust and economically significant relationship between privatization, foreign bank entry, market structure, and banking efficiency. Similarly, macroeconomic variables can explain little of the over-time variation in bank spreads. Bank-level characteristics, on the other hand, such as bank size, operating costs, and composition of loan portfolio explain a large proportion of cross-bank, cross-time variation in spreads and margins. However, time-invariant bank-level fixed effects explain the largest part of bank variation in spreads and margins. Further, the authors find tentative evidence that banks targeting the low end of the market incur higher costs and therefore higher margins